Pengambilan Keputusan Manajerial: Opsi sewa atau beli dalam pengadaan kendaraan dinas - Zanuar Arifin; Ali Tafriji Biswan (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2020)
This study discusses managerial decision making regarding buying or rental (leasing) options in the procurement of official vehicles. This study aims to analyze the most appropriate options between buying or rental (leasing) for the procurement of official vehicles so that they can be input in making decisions regarding procurement of official vehicles. There are differences of opinion regarding the most efficient method of buying or (leasing) rental options in several government agencies so a study is needed to choose the most appropriate method. Differences in decision making related to procurement of official vehicles can have an impact on budget efficiency. This research is a qualitative research with a case study approach. Case studies were conducted at the Secretariat General of the Ministry of Finance. The data used in this study include primary data in the form of interviews with research resource person and secondary data in the form of regulations and reports related to official vehicles. The method of analyzing data from interviews uses the Miles and Huberman method which consists of 3 stages, namely data reduction, data display, and conclusion drawing. Secondary data were analyzed by calculating the net present value of the total cost of ownership. The results of this study indicate that under normal conditions, buying options are relatively more efficient compared to (leasing) rental options in the procurement of official vehicles. However, (leasing) rental options can be applied under certain conditions.